Circadian and Noncircadian Modulation of Autophagy in Photoreceptors and Retinal Pigment Epithelium - Jingyu Yao; Lin Jia; Shameka J. Shelby; Anna M. Ganios; Kecia L. Feathers; Debra A. Thompson; David N. Zacks (2014)
Autophagy in photoreceptors and the RPE promotes homeostasis and survival. The purpose of this study is to determine the daily pattern of changes in autophagy and factors contributing to its regulation in the outer retina.Levels of autophagy markers in the retina and RPE were evaluated over a 24-hour period. To assess the role of phagocytosis in stimulating autophagy in the RPE, cultured RPE-J cells were incubated with isolated photoreceptor outer segments and levels of autophagy markers were measured. Electron microscopy was performed on retina sections and RPE-J cells to assess formation of double-membraned vesicles consistent with autophagosomes.In wild-type C57BL/6 mice maintained under normal cycling light conditions, autophagy in photoreceptor cells and the RPE exhibited a bimodal pattern of activation. In photoreceptors, shifts between light and dark evoked a sharp decrease in autophagy that was followed by a time-dependent increase. In photoreceptors, translocation of transducin and arrestin from the outer to inner segment appeared to contribute to the light-dependent upregulation of autophagy. In contrast, the cyclic variations in RPE autophagy were independent of lighting conditions, and are triggered, at least in part, by ingestion of outer segments.Activation of autophagy in the outer retina exhibits a bimodal pattern that correlates with shifts in transduction proteins within the photoreceptor and by circadian ingestion of outer segments in the RPE. These dynamic shifts suggest a critical role for this pathway in maintaining homeostasis, with further study needed to define the mechanisms underlying the regulation of this phenomenon.